Management of complicated crown fracture by reattachment with super bond: A case series - Verma, Promila; Bains, Rhythm; Tikku, Aseem Prakash; Singh, Meena (Indian Journal of Case Reports, 2018)
Coronal fracture of teeth is a prevalent form of dental trauma. Mainly it affects anterior teeth due to accidental injury, but sometimes posterior teeth may also get affected. The immediate restoration of the original fractured segment not only offers an alternative treatment in the emergency but also restores patient